PENANGGULANGAN TINDAK PIDANA KORUPSI DALAM PERSPEKTIF PENGGUNAAN WEWENANG OLEH PEJABAT PUBLIK - Sugiantari, Anak Agung Putu Wiwik (Jurnal Advokasi, 2017)
Corruption is a latent danger of the implementation of the life of the nation and the State. Increasing number of corrupt behavior indicates that the country suffered a setback. Corrupt behavior arise as a result of violation of ethics (moral) and a violation of law public officials. Public officials can be guilty of corruption because they have high power and authority in determining an important decision in the society so, the authority that causes them to provide benefits for those who have a particular interest. Therefore, the legal system formed during a system that form the characteristic bad because both in terms of structure, substance and culture of law contained in the legal system impacts corrupt behavior as in terms of recruitment and appointment of public officials who are not fair, then legal substances that do not provide a deterrent effect for the perpetrators of corruption and negative about the legal culture habits as if legalized bribery and gratuities. Thus, forming the characteristics of public officials culpable and justifies any means to enrich themselves for the onset of legal awareness of all the elements of the State.